ESTABLISHING A GLOBAL SYSTEM FOR RADIATION AND CHEMICAL SECURITY MONITORING: IMPORTANCE AND OPPORTUNITIES FOR INTERNATIONAL COOPERATION - Akhundov, Ramil (Collection of scientific papers «ΛΌГOΣ», 2025)
As radiation and chemical risks increasingly impact global security, the need for an effective, integrated monitoring system has become critical. This article examines the challenges and opportunities associated with creating a global system for monitoring radiation and chemical threats. It highlights the limitations of current national monitoring systems, the importance of real-time data sharing, and the necessity of global cooperation. The article proposes a framework that includes satellite data, ground-based sensors, and AI-driven analytics to enhance detection, forecasting, and response. Through international collaboration, this system would improve global preparedness, minimize environmental and health risks, and contribute to a more secure world.